Biossegurança alimentar da proteína antifúngica Mo-CBP3 de sementes de Moringa oleifera Lam: uma candidata para o desenvolvimento de plantas transgênicas - Pinto, Clidia Eduarda Moreira (2014)
Mo-CBP3 is a chitin binding protein purified from Moringa oleifera seeds which has an apparent molecular mass of 18.0 kDa and consists of multiple heterodimeric isoforms. Mo-CBP3 is a highly stable protein that has a broad spectrum of activity against phytopathogenic fungi and maintains its secondary structure and antifungal activity at extreme temperatures and different pH values. Thus, the Mo-CBP3 protein presents itself as a promising tool for the development of transgenic plants resistant to fungi attack. For such purpose, the Mo-CBP3 protein was subjected to food safety tests to ensure the safety of its expression in plants, minimizing the risk to non-target animals, which include human beings. The food safety assessment of the protein followed the two-tiered approach, based on weight of evidences, proposed by International Life Sciences Institute (ILSI). The research evidenced the long history of safe use, supported by scientific literature, of the M. oleifera species, source of Mo-CBP3 protein. In silico analysis did not reveal any identity of Mo-CBP3 with allergenic, toxic and/or antinutritional proteins. Additionally, were not found in the protein potential epitopes able to lead to cross reaction and unleash an allergic response. Identity with allergenic proteins was found only when a window of 80 amino acids was used. Potential sites of N-glycosylation were not found in the mature protein. The protein showed resistance to thermal treatment and digestibility by simulated gastric fluid, but was completely susceptible to digestion in simulated intestinal fluid. In addition, Mo-CBP3 caused no relevant adverse effects to mice subjected to high oral doses from 5 to 2000 mg/kg, showing its innocuous nature. Based on the food safety approach proposed by ILSI is not expected any risk associated to use of Mo-CBP3 protein for humans and other monogastric animals.